Effects of training adaption in endurance athletes with atrial fibrillation: protocol for a multicentre randomised controlled trial - Andre La Gerche; Arnljot Tveit; Marius Myrstad; Jon Magne Letnes; Guido Claessen; Turid Apelland; Amy Mitchell; Kristel Janssens; Hielko Miljoen; Eivind Sørensen; Jan Pål Loennechen; Andreas Berg Sellevold; et al. (BMJ Open Sport & Exercise Medicine, 2023)
Trial registration number NCT04991337.Study protocol version 4.7 (Date 9 March 2023).